2020
DOI: 10.1186/s13014-020-01665-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/IIa trial of androgen deprivation therapy, external beam radiotherapy, and stereotactic body radiotherapy boost for high-risk prostate cancer (ADEBAR)

Abstract: Background To evaluate the clinical outcomes of combination of androgen deprivation therapy (ADT), whole pelvic radiotherapy (WPRT), and stereotactic body radiotherapy (SBRT) boost in high-risk prostate cancer patients. Methods This prospective phase I/IIa study was conducted between 2016 and 2017. Following WPRT of 44 Gy in 20 fractions, patients were randomized to two boost doses, 18 Gy and 21 Gy, in 3 fractions using the Cyberknif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The cumulative incidence of GU and GI grade 2 toxicity was quite moderate, measured at 1.4% and 9.3%, respectively, and the 3-year biochemical relapse-free survival was nearly 90%. The second study from Korea explores an SBRT total boost dose question ( 25 ). Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative incidence of GU and GI grade 2 toxicity was quite moderate, measured at 1.4% and 9.3%, respectively, and the 3-year biochemical relapse-free survival was nearly 90%. The second study from Korea explores an SBRT total boost dose question ( 25 ). Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…An SBRT boost could be a noninvasive alternative to a BT boost after EBRT in intermediate- and high-risk prostate cancer. An SBRT boost has been evaluated in a few early-phase prospective studies, with a short follow-up period of <5 yr [9] , [10] , [11] , except for one [8] . In three of the five series, including ours, a rectal spacer was not used [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…An SBRT boost has been evaluated in a few early-phase prospective studies, with a short follow-up period of <5 yr [9] , [10] , [11] , except for one [8] . In three of the five series, including ours, a rectal spacer was not used [8] , [9] . The SBRT boost was delivered in two to three fractions, except in one phase 1 trial [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posttreatment biopsy and comparative clinical trial data suggest room for further disease control improvement at doses >40 Gy in 5 fractions, with limited toxicity data (13,14). Brachytherapy boost treatments have shown that escalating the biological dose of RT can improve prostate cancer outcomes; however, this modality consists of invasive treatments associated with increased toxicity and technical requirements (26)(27)(28). SAbR offers a promising and non-invasive alternative to brachytherapy for improving localized PCa outcomes.…”
Section: Discussionmentioning
confidence: 99%